2017
DOI: 10.5123/s1679-49742017000300005
|View full text |Cite
|
Sign up to set email alerts
|

Tendência temporal da prevalência de hipertensão arterial sistêmica e diabetes mellitus entre adultos cadastrados no Sistema Único de Saúde em Florianópolis, Santa Catarina, 2004-2011*

Abstract: the occurrence of the investigated diseases doubled from 2004 to 2011. However, the prevalences found are below the ones described in the Brazilian scientific literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
14

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 0 publications
0
5
0
14
Order By: Relevance
“…It can be observed that in the Brazilian elderly population, little has been analyzed beyond the prevalence data. 7 - 10 Brazilian population surveys carried out in the last 20 years, considering the adult population aged > 20 years, showed a prevalence of AH varying from 28.5% in the Southeast region 11 to up to 53.2% in the Northern region of the country. 12 In this latter study, the rate of knowledge of the diagnosis was 63.1% and the treatment rate was 85.4%, 12 albeit not specifically among the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that in the Brazilian elderly population, little has been analyzed beyond the prevalence data. 7 - 10 Brazilian population surveys carried out in the last 20 years, considering the adult population aged > 20 years, showed a prevalence of AH varying from 28.5% in the Southeast region 11 to up to 53.2% in the Northern region of the country. 12 In this latter study, the rate of knowledge of the diagnosis was 63.1% and the treatment rate was 85.4%, 12 albeit not specifically among the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…O segundo grupo de fracassos é a insuficiente qualidade no manejo dos fatores de risco e das condições crônicas, incluindo as de saúde mental. Nos últimos 10 anos, apesar do avanço diagnóstico e terapêutico, seguimos com baixas taxas de controle das principais doenças crônicas (hipertensão arterial, diabetes, cardiopatia isquêmica, asma, doença pulmonar crônica obstrutiva (DPOC), problemas osteomusculares) 7,8 e vimos o aumento dos problemas de saúde mental causarem inúmeros prejuízos sociais, principalmente para os indivíduos e suas famílias, mas também para o universo produtivo do emprego e da renda. Paralela e contraditoriamente, por exemplo, houve aumento considerável da oferta da estrutura dos serviços habilitados ( O primeiro era composto em parte por uma parcela fixa, calculada a partir do tamanho populacional do município, o chamado "PAB fixo".…”
Section: Introductionunclassified
“…As doenças crônicas não transmissíveis (DCNT) estabelecem um problema de saúde pública e têm contribuído para a elevação da mortalidade, hospitalizações e perda de qualidade de vida. Entre as DCNT mais prevalentes na população estão a o diabetes mellitus e a hipertensão arterial (TORTORELLA et al, 2017;FRANCISCO et al, 2018;STOPA et al, 2018).…”
Section: Introductionunclassified
“…No Brasil, em 2011 a população com idade de 18 anos ou mais apresentava diagnóstico de hipertensão com 22,7% e 5,6% com diabetes, com prevalência maior em indivíduos de mais idade e de menor nível educacional (TORTORELLA et al, 2017;STOPA et al, 2018).…”
Section: Introductionunclassified